Efeito da progesterona exógena na produção de embriões em novilhas leiteiras - SANTOS, Klayto José Gonçalves dos (2010)
The reproductive and productive index of dairy cattle in Brazil are below the desirable rates, and, in recent decades, the increase in milk production occurred, partly, more because of the expansion of explored areas and the increase of herds than due to an effective productive increment. The development and application of reproductive biotechnologies are essential conditions for improving reproductive efficiency, especially for domestic ruminants, and techniques such as artificial insemination and embryo transfer have been successfully used. Other biotechnologies such as in vitro embryo production, cloning and genetic modification help to accelerate genetic improvement, because they include animals with superior desirable traits, although the results in terms of production are not so good. The main goal of an embryo transfer program is to obtain a high number of viable embryos per donor, after exogenous hormones administration, by increasing the number of oocytes released, enabling the embryo transfer to recipient cows in order to complete the gestation. Cows are born with more than 100,000 oocytes in ovarian follicles, but by natural via, only 0.01% of viable products can be generated, or a number close to 10 calves throughout their reproductive life. One of the proposed solutions to this problem was the development of in vitro production (IVP) of bovine embryos, a major biotech assisted reproduction, which allows the interaction of sperm with oocyte outside the female reproductive tract. Although these biotechnologies are used in many dairy and beef herds, efficiency of an IVP program is limited, among other factors, because of the oocyte recovery rates and the individual variation of ovarian response to FSH treatment, requiring more studies to evaluate the association between follicular waves and superstimulatory treatments, mainly in dairy animals.